SOCIAL MEDIA MARKETING, ELECTRONIC WORD OF MOUTH DAN CUSTOMER ENGAGEMENT - Yudhi Prasetya Mada (Kompetensi (Competence : Journal of Management Studies), 2020)
Internet availability in general has given someone the opportunity to use social media, to interact without the need for physical meetings. However, nowadays social media is not only used as a medium of communication between individuals, but has become an important part in business marketing strategies. For companies, social media can be used as a medium for marketing their products, namely social media marketing. The form of exchange of information and knowledge online on social media is known as an electronic word of mouth. Providing information on the presence of new products, companies can also grow, maintain and increase customer engagement by sharing information and product education. Activities Customer engagement through social media are important to improve the relationship between the company and customers its. This study aims to determine the effect of social media marketing and electronic word of mouth on customer engagement on followers Instagram @ essenzo.indonesia. The research method used is a quantitative approach and uses non-probability sampling with a sample of 100 respondents. Data collection techniques used are using a questionnaire and will be analyzed using path analysis. The results obtained that social media marketing affect customer engagement, so does electronic word of mouth affect customer engagement, then social media marketing and electronic word of mouth affect customer engagement.